Compensatory treatment for hyperdivergent skeletal Class II using temporary anchorage device - Vilela, Luíza T.; Koerich, Leonardo; Silver, Katherine Judith C. M. P.; de Souza, Margareth Maria G.; Ruellas, Antônio Carlos de O. (Brazilian Journal of Health and Biomedical Sciences, 2023)
Introduction:Treatment of hyperdivergent skeletal Class II is one of the most challenging for orthodontists. With the advent of temporary anchorage devices, patients who previously had an indication of orthognathic surgery may be favored with counter-clockwise rotation of the mandible, resulting from vertical control of the posterior teeth. Also, cases with increased incisors display at rest may benefit from these biomechanics in the anterior segment. Methodology and resources:This case report illustrates a successful treatment of a patient with hyperdivergent skeletal Class II malocclusion with an unaesthetic smile involving excessive gingival display at smile and absence of passive lip seal. Results: This way, a suitable functional and aesthetic result was obtained with the correction of the increased gingival exposure, passive lip sealing and improved angulation of the mandibular plane.In addition to the conventional cephalometric superimposition, three-dimensional superimposition was performed and evaluated to validate the treatment outcome.Discussion: Although it does not replace orthognathic surgery, such a modality of treatment may benefit patients who are not willing to undergo a more invasive procedure.